EFFECT OF FILLER NANO TITANIUM DIOXIDE (TiO2) PARTICLES ON FLEXURAL STRENGTH OF NYLON THERMOPLASTIC DENTURE BASE - Muhammad Jodie Setiawan; Rahmat Hidayat; Muh Dian Firdausy (Jurnal Medali, 2022)
Background: Treatment of missing teeth can be done by using dentures. One of the denture base materials is thermoplastic nylon. The advantage of thermoplastic nylon are flexible and deformable. Various attempts have been made to maximize the quality of the denture, for example, by adding TiO2. TiO2 can be used as a filler. Filler is the process of adding TiO2 to the denture base. The advantages of TiO2 particles are  non-toxic, antimicrobial, and increasing the mechanical strength of denture bases.TiO2 can reduce the porosity of the denture.Method: the design study is  a post test only control group with a total of 27 samples. Flexural test was performed using the UTM GD 1100. The statistical test used by the One Way Anova test.Result: The results showed that there were no significant effect on the flexural strength of thermoplastic nylon with the addition of 1% and 5% TiO2 with the control group. The highest flexural strength was obtained in the treatment group of TiO2 1 %, which was an average of 133.3867 N/mm2 and the lowest flexural strength was obtained in the control group without the addition of TiO2, which was an average of 127.57378 N/mm2. The lowest flexural strength was found in the control group without the addition of TiO2, which was an average of 127.57378 N/mm2. Conclusion: There were  no significant effect on the flexural strength of thermoplastic nylon with 1% and 5% TiO2 added with the control group.